A critical review on restoration of grassland ecosystems: Challenges, strategies and future directions - Harish, A; Baranidharan, K; Manivasakan, S; Hemalatha, P; Tilak, M; Ravi, R; Madesh, R (Plant Science Today, 2025)
Grasslands, covering 40 % of global biomes, are crucial for maintaining biological and human life, food security, tourism and climate change mitigation. However, these ecosystems face significant threat from climate change, overgrazing and unsustainable practices like land-use change, leading to declines in biodiversity, productivity and ecosystem resilience. This review aims to identify factors promoting grassland degradation, analyze patterns of degradation and the assessment methods, with a focus on remote sensing and GIS (Geographical Information System) application and evaluate restoration practices and technologies using mechanical, biological and chemical approaches incorporating climate change resilience techniques. Key socio-economic and policy issues challenges include inadequate funding incentives and disjointed governance systems, necessitating stakeholder engagement and sustainable funding. To combat degradation, this study emphasizes the importance of integrating native knowledge from local communities with modern methods and adopting transdisciplinary and climate-resilient approaches for enhanced grassland restoration successes. This study emphasizes on effectively restoring grasslands, improve ecosystem robustness and advance the sustainable development agenda.